POPULASI BAKTERI PENAMBAT NITROGEN SIMBIOTIK PADA RIZOSFER BEBERAPA VEGETASI PIONIR DI LAHAN BEKAS ERUPSI GUNUNG API MERAPI - , TRI NUGROHO JATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Land affected by Merapi volcano eruption was occupaid by pioneer vegetations, such as Leguminosae. Rhizosphere effect of these vegetations on Rhizobium population was not known yet. The purposes this research was to know Rhizobium populations in the rhizosphere of vegetation in areas affected by Merapi volcano eruption. This research was conducted in Kaliadem and Kalitengah Lor. Samples were taken from the rhizosphere of vegetations (Trema orientalis, A. decurrens, Pennisetum purpureum, dan Ptridophyta) and soil without vegetation, each with 3 replications. Variable vegetation observed were amount and effectiveness of root nodules. Nitrogen-fixing bacteria population was counted by the Plate count method. The coloni were isolated, identified and tested for the ability of root nodule formation in Acacia decurrens seedlings. The analysis used was quantitative descriptive analysis. The greatest effective number and nodules were found in Trema orientalis (25.6 nodules/plant, 83.68%) followed by A. decurrens (12 nodules/plant, 75.04%) growing in Kaliadem area. In Kalitengah Lor area, root nodules were found in A. decurrens (10.3 nodules/plant, 46.46%). The mean number of Rhizobium in the rhizosphere of vegetation in Kalitengah Lor was 3.23 x 106 CFU/g and without vegetation 2.44 x 106 CFU/g. The mean number of Rhizobium cell in the rhizosphere in Kaliadem was 1.91 x 106 CFU/g and no vegetation was 1.27 x 105 CFU/g. Isolation has obtained 24 isolates. Rhizobium isolates (6 isolates) formed spherical colonies, convex, white to milky white in color, and have a short rod cell morphology and gram negative. Root nodule formation experiment in A. decurrens seedlings found that the isolates did not form root nodule.